Introduction to the Special Issue on Functional Neuroimaging of the Emotional Brain - Shackman, Alexander J. (Neurosci Lett, 2018)
Recent years have witnessed an explosion of popular and scientific interest in understanding how emotions arise in the brain. Here, we provide an introduction to the Special Issue on Functional Neuroimaging of the Emotional Brain, highlighting some of the most interesting and important recent advances in this burgeoning area of research.